The quest for spirituality: contribution of Tasawwuf to humanity - Abdullah, Fatimah; Bahari, Che Amnah (IIUM and IIIT, 2022)
Islamic literature such as, Tasawwuf provides various and integrated approaches in managing emotions. It is Tasawwuf as the science of the soul deals with self-knowledge, the inner dimension of the human being for the purpose of moulding human personality or character. Islam as a way of life and a worldview offers its followers insights to treat the malaise of the soul in holistic, cognitive, rational and psycho-physiological ways. It is generally acknowledged that, spiritual cognitive therapy can have a significant impact on the treatment of emotional and spiritual disorders. In fact, most of the early Muslim scholars such as al-Ghazali al-Muhasibi and al-Balkhi were Islamic psychologists or Sufis who did their best to spiritually invigorate their disciples and refine their character. This approach of sufi ethics or Tasawwuf with its self-introspection in nature will serve as underpinning of individual and societal wellbeing and mental health that conditioned the development and prosperity of the ummah.